Effect of magnetically treated water on enzymes and total protein in seminal plasma of Holstein bulls born in Iraq: Kreem Iwaid AL-Badry1, Sadeq Jaafer Zalzala1, Faris Faisel Ibrahim2 and Wafa’a Yeedam Lateef2 - AL-Badry, Kreem Iwaid (The Iraqi Journal of Veterinary Medicine, 2017)
Some enzymes of seminal plasma such as, Glutamic oxaloacetic transaminase, Glutamic Pyruvic transaminase, Acid phosphatase and Alkaline phosphatase are essential for metabolic processes which provide energy for viability, motility and fertility of spermatozoa. These enzymes are used as good indicators of semen quality as they measure the plasma membrane stability of spermatozoa, so the aims of study are to estimate the enzymes level and total protein in seminal plasma of Holstein bulls. In present the available knowledge there is no study in Iraq regarding the effect of using magnetically treated water on enzymes and total protein in seminal plasma of Holstein bulls born in Iraq to improve the Artificial Insemination programs. Sixteen bulls were divided equally into two groups depending on their age. Young (17-19 months) and adult (29-32 months), then randomly distributed into two equal sub groups (control and treatment) through February until June months. Treatment group was given magnetically treated water which passed through magnetic device with strength of 2000 gauss; control group was given normal water without magnetism. Results show that there is a monthly variation in levels of enzymes, in the group drinking magnetic water effect significantly (P<0.05), all enzymes of seminal plasma of Holstein bulls in Iraq, with no effect on total protein.